Perceptions through a prism : three accounts of good social work supervision : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University, Palmerston North, New Zealand - Davys, Allyson (Massey University, 2002)
This thesis explores the elements of 'good' social work supervision from the perspective of the participants of supervision, analyses a supervision session between one supervision dyad and considers this data against the theories and models presented in the literature. A qualitative methodology was adopted using in-depth interviews and a focus group to identify the characteristics of good supervision from the perspective of the supervisee. A similar methodology was used to interview the supervisors of these supervisees. The supervisors were asked to discuss the supervision which they provided and the beliefs and theories which guided their practice. The reports of these two groups were supported by the analysis of a recorded supervision session between one of the supervision pairs. The findings indicated four key elements to good supervision:- the qualities and attitudes brought by the supervisee, the qualities and the attributes brought by the supervisor, the element of choice within the relationship and the nature of the supervision relationship itself. The role of choice was considered to be of particular significance to the success of supervision, promoting commitment and deepened responsibility from both supervisor and supervisee. It was also noted that all of the supervisors and four of the six supervisees had training in supervision and it is suggested that this training promotes the ability of both of the participants to produce 'good' supervision. Two recommendations are made: that social work managers consider ways to introduce choice of supervisor to all social workers and that supervision fraining is encouraged for all social workers The relative merits and roles of internal and external supervision are discussed and, following suggestion from the data, a re-vision of supervision is proposed which moves social work supervision from a single relationship into a framework of different services and relationships.
Keywords: Social workers; Supervision of; Supervisors; Supervision of employees; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Social work